An Analysis and Editio Princeps of Fakhr al-Dīn al-Rāzī’s Risālah: Al-Jawhar al-Fard - Eşref Altaş (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
This article examines Fakhr al-Dīn al-Rāzī’s Al-Jawhar al-Fard, which analyses the concept of atomism held by theologians. This article introduces its extant copies; establishes its name, date of writing, and chronology in relation to the author’s other works; proves al-Rāzī’s authorship; and, finally, edits the text. As the next step, the issues addressed by the text are identified; al-Rāzī’s critiques of the arguments in favor of and against atomism are discussed; the geometrical arguments, which hold an important place in the treatise, are examined, and his ideas on relations between geometry and atomism are reviewed. Al-Rāzī’s various attitudes towards atomism are presented in chronological order. The geometrical figures are drawn to provide a better understanding of the arguments of al-Rāzī. In the Appendix, all arguments are shown in tables.